Analyzing of HEC-RAS based geodata basis from the aspects of the EU Water Framework Directive - Pregun, Csaba; Tamás, János; Takács, Péter; Bíró, Tamás (Acta Agraria Kaposváriensis, 2006)
The HEC-RAS hydrological software is suitable for modeling natural and artificial water bodies and river networks, including hydraulic structures. The program able to simulate the effects of emergency water reservoirs, dam breaks; visualize, track and calculate floods and possible flooded areas at given water level. The program calculates several actual hydraulic data of the riverbed, and handles the both inputs and outputs in georeferenced ArcView GIS environment. The complex GIS database in our Department contains detailed information on the geographic, geologic, land use, slope, runoff, soil, etc. features of the Bihar-Plain. The data exchange between the GIS and the hydrologic database offers the opportunity to calculate predictions for the suitable and necessary surface watershed control for environmental and landscape protection purposes.
Keywords: hydrological and GIS model; environmental and landscape protection; watershed management